Seroprevalence and risk factors of Toxoplasma gondii in ruminant meats from wet markets in Klang Valley and abattoirs in Selangor, Malaysia - Abdul Hamid, Norhamizah; Sadiq, Mohammed Babatunde; Ramanoon, Siti Zubaidah; Mansor, Rozaihan; Watanabe, Malaika; Md Isa, Nur Mahiza; Kamaludeen, Juriah; Syed Hussain, Sharifah Salmah (MDPI AG, 2020)
(1) Background: The objective of this study was to determine the prevalence of T. gondii in meats of cattle, goat and sheep from wet markets in Klang Valley, and abattoirs in Selangor, Malaysia; (2) Methods: A total of 192 meat samples were purchased from 51 wet markets in six districts in Klang Valley (Gombak, Klang, Kuala Lumpur, Hulu Langat, Petaling and Putrajaya). Meanwhile, a total of 200 diaphragm samples were collected from two government abattoirs located in Shah Alam and Banting, Selangor. All meat juices from samples were subjected to an indirect-ELISA kit for the presence of T. gondii IgG antibodies. Furthermore, all 184 meat samples of goat and sheep were subjected to conventional nested PCR (B1 genes) for the detection of T. gondii DNA; (3) Results: T. gondii antibodies were detected in 25% (n = 98/392) of the samples with seroprevalence of 9.1% (19/208, CI: 5.9%–13.8%) in cattle meat; 54.7% (41/75, 95% CI: 43.5%–65.4%) in goat meat and 34.9% (38/109, CI: 26.6%–44.2%) in sheep meat. No T. gondii DNA was detected in any of the meat samples of goat and sheep. T. gondii seropositivity in wet market samples was higher in goat (OR = 37.1 CI 12.4–110.3) and sheep meat (OR 9.03 CI: 3.28–24.8) compared to cattle meat (OR = 1.0) At univariate level, meat from non-licensed abattoirs (OR = 6.0 CI: 2.9–12.3) and female animals (OR = 6.7; CI 1.9–22.6) had higher risks of being seropositive for T. gondii antibodies than licensed abattoirs and male animals, respectively. (4) Conclusions: This is the first report of seroprevalence of T. gondii in ruminant meats for human consumption in Malaysia. The findings signified high exposure of meat samples from wet markets to T. gondii and the need for control measures to reduce the likelihood of infection when such raw or undercooked meats are consumed.